Development of a Lecture Monitoring Information System for Management Department at the State University of Medan - Haryadi, Haryadi; Rahman, Haikal; Aprinawati, Aprinawati; Prayogo, Rangga Restu; Syahreza, Dina Sarah; Syah, Dedy Husrizal (Universitas Negeri Padang, 2025)
The development of information technology, especially websites, is necessary to increase the efficiency and accuracy of monitoring and evaluating lectures in higher education, especially during the Covid-19 pandemic. This study aims to develop a web-based lecture monitoring information system and test the feasibility level of the information system developed based on validation/assessment from a team of experts and students. This research uses a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). System designed using Appsheet with Google Sheets database. Media Validation was carried out by a Visual Media Expert Lecturer and tested on 70 class commissioner students in the management department at State University of Medan. In general, the results of the media aspect validation as measured by two indicator aspects of interface and multimedia are classified as very feasible at 88.89%, and the results of the field trial assessment as measured by four indicator aspects of correctness, reliability, integrity, and usability are also categorized as very feasible at 89.89%.